Building Trust for Sustainable Land Rehabilitation: Community Involvement and Management Post-Mining - Agung Dwi Sutrisno; Erry Sumarjono; I Wayan Koko Suryawan; Bih Chuan Lin (CV FOUNDAE, 2025)
Post-mining land use sustainability is critical for mitigating environmental degradation and ensuring long-term community benefits. This study identifies gaps in participation and highlights innovative strategies for addressing trust deficits in land management. Through advanced statistical methods such as Structural Equation Modeling (SEM), the research pinpoints the pivotal role of transparency and trust-building in driving community engagement. Additionally, the study explores the implications of global best practices in land rehabilitation and how these can be adapted to local contexts like Pongkor, Bogor Regency. By integrating insights from international case studies, this analysis underscores the need for tailored community outreach programs that align with cultural and socioeconomic dynamics. The findings contribute to broader discussions on sustainable practices and provide actionable recommendations for policymakers to enhance the effectiveness of post-mining rehabilitation efforts.